The new food activism : opposition, cooperation, and collective action - Alkon, Alison Hope; Guthman, Julie (University of California Press, 2017)
"New and exciting forms of food activism are emerging as supporters of sustainable agriculture increasingly recognize the need for a broader, more strategic and more politicized food politics that engages with questions of social, racial, and economic justice. This book highlights examples of campaigns to restrict industrial agriculture's use of pesticides and other harmful technologies, struggles to improve the pay and conditions of workers throughout the food system, and alternative projects that seek to de-emphasize notions of individualism and private ownership. Grounded in over a decade of scholarly critique of food activism, this volume seeks to answer the question of "what next," inspiring scholars, students, and activists toward collective, cooperative, and oppositional struggles for change."--Provided by publisher